Varying ethics rules in clinical research and routine patient care – research ethics committee chairpersons’ views in Finland - Hemminki, Elina (BioMed Central, 2014)
BACKGROUND: To present empirical data on how the variation in regulating clinical research and patient care was perceived in Finland between 2009 and 2012. METHODS: Notes of interviews with 22 research ethics committee (REC) chairpersons were analyzed to identify whether differences in the regulation of clinical research and patient care were addressed. REC chairpersons’ opinions on three imaginary cases of clinical research projects challenging current research ethics rules (vignettes) were requested with a questionnaire; 18 of the 22 interviewed chairpersons responded. RESULTS: Based on REC chairpersons’ interviews, the differences between care and research regulation were not considered important issues in Finland. In the vignettes, REC chairpersons’ assumptions on how their REC would decide varied in regard to allowing research without informed consent, while solutions that are not allowed by current law were even anticipated. Mostly, but not always, the chairpersons’ own personal view agreed with their REC. CONCLUSIONS: The distinction between care and research regulation has not been publicly challenged by Finnish RECs, even though it is a challenge when research relevant to health care is carried out. There is a need for debate and changes in laws and practices.